The relationship between risky decision making and situational factors - Endriulaitienė, Auksė; Martišius, Vaclovas (Psichologija, 2002)
Recent social theory proposes the idea that the risk society is developing, so the problems of risky decision making are more and more urgent. There are a lot of investigations in the field of situational correlates of risky decision making (e. g., problem framing, task difficulty, etc.). But there is not clear if the problem content has the impact upon the propensity to make risky decisions. The goal of this work was to test hypothesis that people are more prone to risky decision making in health and monetary risk area than in social and ethical risk area. Participants were 602 subjects (age 18-60; 262 students and 340 workers). They completed Kogan and Wallach's (1964, 1967) Choice Dilemma Questionnaire (CDQ), where they had to choose the appropriate for them probability for risky decision in twelve situations (from monetary, health, social and ethical risk areas). The results showed that people make the most risky decisions in health risk area and the safest decisions in ethical risk area. But the relationship between risk area and risky decision making may be mediated by individual factors (e. g., gender and age).
Keywords: risky decision making; situational factors